Chemically Modified Electrodes in Electrochemical Drug Analysis - Kaya, Sariye I.; Karabulut, Tutku C.; Kurbanoglu, Sevinç; Ozkan, Sibel A. (Current Pharmaceutical Analysis, 2020)
Electrode modification is a technique performed with different chemical and physical methods using various materials, such as polymers, nanomaterials and biological agents in order to enhance sensitivity, selectivity, stability and response of sensors. Modification provides the detection of small amounts of analyte in a complex media with very low limit of detection values. Electrochemical methods are well suited for drug analysis, and they are all-purpose techniques widely used in environmental studies, industrial fields, and pharmaceutical and biomedical analyses. In this review, chemically modified electrodes are discussed in terms of modification techniques and agents, and recent studies related to chemically modified electrodes in electrochemical drug analysis are summarized.
Keywords: carbon nanomaterials